2011
DOI: 10.1007/s00296-010-1787-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term response after 6-year treatment with anakinra and onset of focal bone erosion in neonatal-onset multisystem inflammatory disease (NOMID/CINCA)

Abstract: The exact elucidation of skeletal and cartilagineous involvement in neonatal-onset multisystem inflammatory disease (NOMID) is still poorly known, and there are few data providing the long-term response to treatment with the available interleukin-1 inhibitors. We present here a 13-year-old boy with NOMID treated with anakinra and low-dose methylprednisolone since he was 7 years old for an overall period of 6 years. Every clinical manifestation was highly responsive to interleukin-1 blockade, with the exception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 9 publications
0
20
0
2
Order By: Relevance
“…Stimulation of nuclear factor-κB (NFκB) signalling pathways leads to upregulated IL-1B mRNA transcription and increased pro-IL-1B production resolved within 24 hours of dose administration, and this remission lasted 36 hours [27]. Similar symptomatic remission has been reported in CINCA/NOMID patients, together with significant response of acute-phase markers serum amyloid A and C-reactive protein [21,28], although this may not necessarily halt the development of irreversible bone changes [29]. More recently, a single-center observational study of 12 patients with MWS treated with anakinra for a median of 11 months and followed up for the same median time period showed significantly reduced disease activity and improvements in patient-derived health measures in all patients, and improved hearing in 1 patient [30].…”
Section: Human Diseases Associated With Interleukin-1βmentioning
confidence: 61%
“…Stimulation of nuclear factor-κB (NFκB) signalling pathways leads to upregulated IL-1B mRNA transcription and increased pro-IL-1B production resolved within 24 hours of dose administration, and this remission lasted 36 hours [27]. Similar symptomatic remission has been reported in CINCA/NOMID patients, together with significant response of acute-phase markers serum amyloid A and C-reactive protein [21,28], although this may not necessarily halt the development of irreversible bone changes [29]. More recently, a single-center observational study of 12 patients with MWS treated with anakinra for a median of 11 months and followed up for the same median time period showed significantly reduced disease activity and improvements in patient-derived health measures in all patients, and improved hearing in 1 patient [30].…”
Section: Human Diseases Associated With Interleukin-1βmentioning
confidence: 61%
“…It is relevant to note that clinical experience with IL-1Ra in pediatric disease abounds, mainly because auto-inflammatory diseases such as familial Mediterranean fever, hyper-IgD syndrome, cryopyrin-associated periodic syndrome, and systemic juvenile idiopathic arthritis usually present in childhood. Neonatal-onset multisystem inflammatory disease (NOMID) and deficiency of IL-1Ra (a loss-of-function mutation in il1rn) both present in early infancy and are successfully and safely treated with IL-1Ra (17)(18)(19)(20). Importantly, a study in 71 preterm infants identified a low-expression il1rn genotype to be strongly associated with an increased susceptibility to BPD (odds ratio 11.7 (16)).…”
Section: Discussionmentioning
confidence: 99%
“…injection of 150 μg/kg of LPS or volumematched vehicle (normal saline) at 14 d gestation. Within 24 h after birth, pups and dams were randomized to a chamber through which we passed gas at 10 L/min with an FiO 2 of 0.21 (room air), 0.65, or 0.85 for a total of 3, 14, or 28 d. Pups were also randomly allocated to receive daily s.c. injections of IL-1Ra (10 mg/kg) [a moderate dose considering (i) the Food and Drug Administration recommendation to use 12-fold higher drug doses in murine trials to compensate for the species-specific differences in activity and (ii) the dose of 1-5 mg/kg in human infants with NOMID (19)] or a similar volume of vehicle. Temperature (22°C) and humidity (50-60%) were kept constant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal-onset multisystem inflammatory disease (NOMID), the most severe CAPS, is attended by bone loss and skeletal deformation (101,(115)(116)(117)(118). IL-1-blocking agents have limited efficacy against NOMID skeletal lesions, while other symptoms related to systemic inflammation are rapidly resolved (119)(120)(121)(122). While the human disease is phenocopied in mouse models with global NOMID mutation (98,123), mice bearing the mutation only in osteoclasts lack systemic inflammation but have severe osteoporosis (99), indicating a cell-autonomous role in the bone-resorptive cell.…”
Section: Pathogenesis Of Periprosthetic Osteolysismentioning
confidence: 99%